Work Engagement and Flourishing at Work Among Nuns: The Moderating Role of Human Values - Ariza-Montes, Antonio; Molina-Sánchez, Horacio; Ramirez-Sobrino, Jesús; Giorgi, Gabriele (Frontiers in Psychology, 2018)
Faith-based organizations are a key player in major sectors of activity for maintaining the welfare state, including health, education, and social services. This paper uses a multivariate regression model in an attempt to identify the factors that affect the relationship between work engagement and flourishing. The paper also discusses the empirical research gap that has been identified in the literature about the moderated effect of human values on this relationship. This study is based on a sample of 142 nuns of a congregation belonging to a religious organization with an international scope and a Catholic inspiration. The case of religious women who have chosen to live a life consistent with the charism of the congregation constitutes a paradigmatic and unique environment to investigate the potential alignment of personal values with professional activity. Two important conclusions are derived from this work. First, the more engaged nuns are in their work (social action to serve the poorest and most disadvantaged people), the more they flourish in their working environment and in their personal lives. Second, certain personal values reinforce the relationship between the professional role (work engagement) and the personal role (flourishing).